Penerapan 3M dalam Mencegah Penularan Covid-19 di Desa Lonjoboko Kabupaten Gowa - Haeril Amir; Al Ihksan Agus; Muhammad Irfan Maulana Bima; Ihwana As'ad; Muhammad Fachri Hafid; Jabal Rahma Ashar; Abdul Qahar Zainal; Ahmad Jihad; Gusti Hardyanti Musda (PT.Mantaya Idea Batara, 2021)
This community service is carried out as a form of the Tri Dharma of Higher Education, community service with the theme of implementing 3M in preventing the transmission of covid-19 is not without reason but seeing the tendencies and habits of the people who always ignore health protocols, besides that this service is in the form of counseling. The purpose of this service is to educate the public about the impact and influence of Covid-19. The method of implementing community service with direct counseling techniques to the community. The results of the service, in general the counseling participants said that their knowledge of covid-19 was increasing and they were committed to complying with the Health protocol. The conclusion of this service is the importance of continuous education and outreach to the community regarding the effects and dangers of Covid-19.